2019
DOI: 10.1093/jncics/pkz088
|View full text |Cite
|
Sign up to set email alerts
|

Oxybutynin vs Placebo for Hot Flashes in Women With or Without Breast Cancer: A Randomized, Double-Blind Clinical Trial (ACCRU SC-1603)

Abstract: Background Hot flashes (HFs) negatively affect quality of life among perimenopausal and postmenopausal women. This study investigated the efficacy of oxybutynin vs placebo in decreasing HFs. Methods In this randomized, multicenter, double-blind study, women with and without breast cancer with 28 or more HFs per week, lasting longer than 30 days, who were not candidates for estrogen-based therapy, were assigned to oral oxybuty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“… 113 , 114 , 115 , 116 , 117 To control hot flushes, valid alternatives are venlafaxine, oxybutynin, gabapentin and clonidine. 118 , 119 , 120 , 121 Sleep disturbances may be treated with melatonin. 122 , 123 There is no convincing evidence that phytotherapeutic drugs may improve menopausal symptoms.…”
Section: Methodsmentioning
confidence: 99%
“… 113 , 114 , 115 , 116 , 117 To control hot flushes, valid alternatives are venlafaxine, oxybutynin, gabapentin and clonidine. 118 , 119 , 120 , 121 Sleep disturbances may be treated with melatonin. 122 , 123 There is no convincing evidence that phytotherapeutic drugs may improve menopausal symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Hot flushes may be treated with serotonin reuptake inhibitors (i.e., venlafaxine) (LoE 1a/A/AGO+). A recent study found that 2.5 or 5.0 mg oxybutynin twice a day for 6 weeks was an effective treatment option for women with hot flushes [74] (LoE 1b/A/AGO+/–). Homeopathy and phytotherapy had no effect on hot flushes in large randomized trials compared with placebo in breast cancer survivors (LoE 1b/B/AGO–) [75]; interestingly, in these studies a substantial effect was observed also in the control arm (“placebo effect”).…”
Section: Gynecological Issues In Breast Cancer Patients and Contraceptionmentioning
confidence: 99%
“…In large randomized controlled trials, paroxetine, escitalopram, citalopram, desvenlafaxine and venlafaxine have been associated with statistically significant reductions in hot flush severity (Table 1). 4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Sertraline and fluoxetine have shown inconsistent, modest or insignificant improvements in menopausal symptoms. 12,16,17 Paroxetine salt, paroxetine mesylate (7.5 mg daily), was shown to effectively reduce the severity and frequency of menopausal vasomotor symptoms in two randomized controlled trials of 12 and 24 weeks' duration.…”
Section: Selective Serotonin Reuptake Inhibitors and Serotonin Norepinephrine Reuptake Inhibitorsmentioning
confidence: 99%